THE INFLUENCE OF SOCIAL MEDIA MARKETING, FINANCIAL LITERACY,RISK PERCEPTION, AND USER SATISFACTION ON PAYLATERCONSUMER LOYALTY IN INDONESIA - Sri Nurhasana; Wulan Dari; Kurnia Tika; Erny Wahyuni; Tetty Rahmiati Harahap (INDONESIAN JOURNAL OF BUSINESS AND ECONOMICS, 2025)
This study aims to analyze the influence of Social Media Marketing, Financial Literacy, Risk Perception, and User Satisfaction on Consumer Loyalty among Paylater service users in Indonesia. Paylater services are increasingly popular among digital communities, but consumer loyalty to this service remains a challenge amidst increasing competition and usage risks. This study uses a quantitative approach with a survey method of 200 active Paylater user respondents. The analysis technique used is multiple linear regression with the help of SPSS software. The results show that Social Media Marketing, Financial Literacy, and User Satisfaction have a positive and significant effect on Consumer Loyalty, while Risk Perception has a negative and significant effect. Simultaneously, these four variables have a significant influence on loyalty, with an F-value of 29.783 and a significance value of 0.000. The coefficient of determination (R²) value of 0.379 indicates that 37.9% of the variation in consumer loyalty can be explained by this model. This study implies that improving digital marketing strategies, financial education, risk management, and user service quality are important steps in building sustainable Paylater consumer loyalty in Indonesia.